Synthesis of wurtzite ZnS nanoparticles using the microwave assisted solvothermal method - La Porta, Felipe A. [UNESP]; Ferrer, Mateus M.; De Santana, Yuri V.B.; Raubach, Cristiane W.; Longo, Valéria M. [UNESP]; Sambrano, Júlio R. [UNESP]; Longo, Elson [UNESP]; Andrés, Juan; Li, Máximo S.; Varela, José Arana [UNESP] (Elsevier, 2013)
In this article, we report the development of an efficient and rapid microwave assisted solvothermal (MAS) method to prepare wurtzite ZnS nanoparticles at 413 K using different precursors. The materials obtained were analyzed by X-ray diffraction (XRD), X-ray photoelectron spectroscopy (XPS), field emission scanning electron microscopy (FE-SEM), transmission electron microscopy (MET) ultraviolet-visible (UV-vis) and photoluminescence (PL) measurements. The structure, surface chemical composition and optical properties were investigated as a function of the precursor. In addition, effects as well as merits of microwave heating on the processing and characteristics of ZnS nanoparticles obtained are reported. The possible formation mechanism and optical properties of these nanoparticles were also reported. © 2012 Elsevier B.V. All rights reserved.
Keywords: Microwave; Nanoparticles; Optical properties; ZnS; Different precursors; Field emission scanning electron microscopy; Formation mechanism; Microwave assisted; Photoluminescence measurements; Solvothermal; Solvothermal method; Surface chemical composition; Wurtzites; ZnS nanoparticles; Field emission microscopes; Microwaves; Photoelectrons; Transmission electron microscopy; X ray diffraction; X ray photoelectron spectroscopy; Zinc sulfide